An unusual secondary extramammary Paget's disease of vulva - Noel, Alvish (Indian J Sex Transm Dis AIDS, 2020)
Extramammary Paget's disease (EMPD) of the vulva is a rare disease that occurs mainly in postmenopausal women. It can be primary or secondary. Prognosis of primary EMPD is good, but when secondary, we need to find the underlying malignancy as the prognosis depends on it. Very few cases of secondary EMPD of the vulva have been reported till now. We hereby report a case of a 65-year-old postmenopausal woman with EMPD secondary to invasive adenocarcinoma with neuroendocrine features in the dermis and she was treated surgically followed by radiotherapy.